Cattle Marketing Strategy In The Livestock Market Suka Village, Tigapanah District, Karo Regency - Sinulingga, A.H.G.; R. E. Mirwandhono; N. Ginting; J.A. Lase (Jurnal Peternakan Integratif, 2023)
Livestock is a sub-sector of rural community economic development, so it must be explored and developed to provide added value to livestock businesses. This study aims to determine  strategy applied to cattle market traders and examine the cost and profits obtained from the livestock market in Suka Village, Tigapanah District, Karo Regency, North Sumatra Province. The study was carried out  from September - October 2021 and used the results of observations and interviews of respondents as primary data. Determination of respondents using snowball sampling method which has 50 respondents. Secondary information is obtained from related parties such as the Central Bureau of Statistics and the Karo Regency Agriculture Office. The parameters studied are institutions, channels, market functions, structure, behavior, market performance, market margins, farmer's share and profit to cost ratio. The results of this study show there are two marketing channels: the first channel: farmer–consumer and the second channel: farmer–collector–consumer. The market performance in this study is that technical development has not improved and the quality of products and services of farmers has not been maximized. Through the first marketing channel, the marketing margin is Rp.0 and the second channel is Rp.815,384. Farmer's share in the first channel is 100% and the second channel is 95.59 %. The profit to cost ratio of channel I is 105-.86 and channel II is 2.55. The conclusion of this study is that the marketing of beef cattle in the livestock market in Suka Village, Tigapanah District, Karo Regency is efficient.